2023
DOI: 10.2147/ccid.s397751
|View full text |Cite
|
Sign up to set email alerts
|

A Proteome-Centric View of Ageing, including that of the Skin and Age-Related Diseases: Considerations of a Common Cause and Common Preventative and Curative Interventions

Abstract: The proteome comprises all proteins of a cell or organism. To carry their catalytic and structure-related functions, proteins must be correctly folded into their unique native three-dimensional structures. Common oxidative protein damage affects their functionality by impairing their catalytic and interactive specificities. Oxidative damage occurs preferentially to misfolded proteins and fixes the misfolded state. This review provides an overview of the mechanism and consequences of oxidative proteome damage –… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 50 publications
0
1
0
Order By: Relevance
“…24 Benoit et al indicated that proteome damage, particularly protein carbonylation, leads to general aging of organisms and organs during aging, while contributing to diseases such as Alzheimer's and Parkinson's diseases, diabetes, psoriasis and skin cancer. 25 Other studies have shown that frailty state can cause an imbalance in the skin flora, leading to a range of host immune-related diseases. 26 Each of these studies had its own focus.…”
Section: Discussionmentioning
confidence: 99%
“…24 Benoit et al indicated that proteome damage, particularly protein carbonylation, leads to general aging of organisms and organs during aging, while contributing to diseases such as Alzheimer's and Parkinson's diseases, diabetes, psoriasis and skin cancer. 25 Other studies have shown that frailty state can cause an imbalance in the skin flora, leading to a range of host immune-related diseases. 26 Each of these studies had its own focus.…”
Section: Discussionmentioning
confidence: 99%
“…The disruption of protein quality control, or proteostasis, leading to the accumulation of oxidized proteins (i.e., protein carbonylation), is a hallmark of both chronological and photo-induced aging in the skin [ 40 ]. Given that this phenomenon occurs in dermal fibroblasts during both intrinsic aging and following UVR exposure, an altered proteome has been recently proposed by Benoit et al [ 41 ] as a central mechanism underlying skin aging. Interestingly, an extract derived from the bacterium Arthrobacter agilis has been identified as a potential novel agent for proteome protection due to its chaperone-like properties [ 42 ].…”
Section: Reviewmentioning
confidence: 99%
“…Interestingly, an extract derived from the bacterium Arthrobacter agilis has been identified as a potential novel agent for proteome protection due to its chaperone-like properties [ 42 ]. Additionally, this extract has shown the ability to protect the skin’s proteome from carbonylation, a process that can lead to protein misfolding and degradation, thereby suggesting its potential for anti-aging applications [ 41 , 42 ]. Glycation, a specific type of protein damage where a sugar molecule interacts with a protein to form advanced glycation end products (AGEs), is another significant contributor to age-related loss of skin proteostasis [ 43 ].…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Proteomics, the comprehensive study of proteins, has emerged as a powerful tool to identify biomarkers in diseased skin [77], which could be potentially useful to develop targeted cosmetic therapies. Other applications in regenerative cosmetics include elucidating cellular processes involved in skin aging, regeneration, and damage [78], and characterizing biocompatible materials used in engineered skin substitutes [79]. In this regard, a recent publication highlighted the importance of the MSCs secretome in the improvement of anti-aging, whitening, and wound healing processes, and its potential use as novel biomaterials for skin regeneration [80].…”
Section: Proteomicsmentioning
confidence: 99%